179k views
4 votes
( x-3 ).( 2x-3 ) = 0

User Tom Gruner
by
4.6k points

2 Answers

5 votes

Answer:


x=3, x=(3)/(2)

Explanation:


\left(x-3\right)\left(2x-3\right)=0

The zero product theorem will be used here to solve this non-linear problem.

means that in the original equation, each variable component must be set to zero.


\begin{cases} x-3=0\\2x -3=0\end{cases}

To solve this linear equation, we need to group all of the variable terms on one side of the equation and all of the constant terms on the other.

so, -3 will be moved to the right side

Notice that when a term moves from one side of the equation to the other, it changes sign.


\begin{cases} (x-3)+3=3\\(2x-3)+3=3 \end{cases}


x\left \{ 3,(3)/(2) \}

OAmalOHopeO

User Drizzt
by
4.9k points
2 votes

Answer:

Explanation:

Assuming you want to find x, we can set two equations:

x-3=0

2x-3=0

This is so that we can individually find x within the two paranthesis and not have to do more work. It helps for standardized tests.

solve for x on both sides, and you get 3 and 1.5

User Ramya S
by
5.2k points